MtuA, a Lipoprotein Receptor Antigen from Streptococcus uberis, Is Responsible for Acquisition of Manganese during Growth in Milk and Is Essential for Infection of the Lactating Bovine Mammary Gland - Smith, Amanda J. (American Society for Microbiology, 2003)
A mutant strain of Streptococcus uberis (AJS001) that was unable to grow in bovine milk was isolated following random insertional mutagenesis. The level of growth in milk was restored to that of the parental strain (strain 0140J) following addition of MnSO(4) but not following addition of other metal ions. The mutant contained a single insertion within mtuA, a homologue of mtsA and psaA, which encode metal-binding proteins in Streptococcus pyogenes and Streptococcus pneumoniae, respectively. Strain AJS001 was unable to infect any of eight quarters on four dairy cows following intramammary challenge with 10(5) CFU. Bacteria were never recovered directly from milk of these animals but were detected following enrichment in Todd-Hewitt broth in three of eight milk samples obtained within 24 h of challenge. The animals showed no inflammatory response and no signs of mastitis. Three mammary quarters on two different animals simultaneously challenged with 600 CFU of the parental strain, strain 0140J, became colonized, shed high numbers of S. uberis organisms in milk, displayed a marked inflammatory response to infection, and showed overt signs of mastitis. These data indicate that mtuA was required for efficient uptake of Mn(2+) during growth in bovine milk and infection of the lactating bovine mammary gland.